The Role of Women in New Testament Ministry and Its Implications for Contemporary Church Practice: A Biblical-Theological Exploration - Jezreel Smith Mietuade (CV Projurnal Mitra Publikasi, 2025)
Women held visible, significant roles in the New Testament church, despite operating within a patriarchal culture that restricted female public and religious participation. Jesus affirmed women as disciples, valued their theological insight, and appointed them as key resurrection witnesses. Early church figures like Phoebe, Priscilla, Lydia, and Junia contributed to teaching, hospitality, financial support, and apostolic work. Yet contemporary debates persist between complementarian and egalitarian views on women in ministry. This study examines the biblical portrayal of women in ministry and its implications for church practice today. The research adopts a qualitative method involving grammatical-historical and lexical exegesis of key New Testament texts and contested ministry terms (diakonos, prostatis, apostolos, kephalē, authentein), a historical survey of early Christian practice from the patristic through the modern period, and theological reflection on unity and equality in Christ through Galatians 3:28 and the pneumatological framework of 1 Corinthians 12 and Acts 2:17. Findings indicate that women were not only participants but also influential leaders in the early church, and that many present day restrictions are more culturally conditioned than biblically mandated. The study concludes that faithful contemporary ministry should affirm the New Testament principle of equality in Christ while discerning cultural expressions responsibly. It recommends that churches intentionally recognize spiritual gifts in women, provide structured leadership development, and foster collaborative ministry models where men and women serve together in advancing the gospel of Jesus Christ.